2016
DOI: 10.1371/journal.pgen.1006346
|View full text |Cite|
|
Sign up to set email alerts
|

Allatostatin A Signalling in Drosophila Regulates Feeding and Sleep and Is Modulated by PDF

Abstract: Feeding and sleep are fundamental behaviours with significant interconnections and cross-modulations. The circadian system and peptidergic signals are important components of this modulation, but still little is known about the mechanisms and networks by which they interact to regulate feeding and sleep. We show that specific thermogenetic activation of peptidergic Allatostatin A (AstA)-expressing PLP neurons and enteroendocrine cells reduces feeding and promotes sleep in the fruit fly Drosophila. The effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
173
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(195 citation statements)
references
References 118 publications
10
173
2
Order By: Relevance
“…Furthermore, co-expression with the pan-neuronal GAL4 repressor nSyb-GAL80 (Rezaval et al, 2012) completely reverted the increased wake phenotype caused by NPF cell activation (Figure S2C). It has been reported that nSyb-GAL80 blocks GAL4 expression both in the nervous system (Rezaval et al, 2012) and AstA- producing EECs (Chen et al, 2016). However, in our hands, nSyb-GAL80 successfully blocked NPF-GAL4 reporter expression in the adult brain, but failed to completely repress expression in the EECs (Figure S2D).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, co-expression with the pan-neuronal GAL4 repressor nSyb-GAL80 (Rezaval et al, 2012) completely reverted the increased wake phenotype caused by NPF cell activation (Figure S2C). It has been reported that nSyb-GAL80 blocks GAL4 expression both in the nervous system (Rezaval et al, 2012) and AstA- producing EECs (Chen et al, 2016). However, in our hands, nSyb-GAL80 successfully blocked NPF-GAL4 reporter expression in the adult brain, but failed to completely repress expression in the EECs (Figure S2D).…”
Section: Resultsmentioning
confidence: 99%
“…Diet-mediated effects on sleep-wake behavior rely on gustatory receptors that converge onto the SOG (Linford et al, 2012), and NPF activity within the SOG may play a role in this response. Beyond the CNS, midgut NPF + EEC effects on nutrient evaluation or feeding cannot be completely ruled out, and both published findings and the data presented leaves open the possibility that the gut-brain axis may utilize neuropeptide signaling, which may include NPF, to properly synchronize feeding with wakefulness (Chen et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…This process is also facilitated through AstA-AKH interactions to maintain the dynamic balance of glucose. AstA is a neuropeptide involved in a series of satiety signals such as feeding, metabolism, and sugar reward [50][51][52]. Its receptor, Allatostatn A Receptor (AstAR), is expressed in both insulin and AKH cells.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, corazonin promotes food intake (Hergarden et al, 2012), while allatostatin A and drosulfakinins inhibit it (Hergarden et al, 2012; Söderberg et al, 2012; Chen et al, 2016). This regulatory activity on peptides with opposing physiological functions indicates that Nep4 affects multiple aspects of feeding control, rather than promoting or inhibiting food intake in a mutually exclusive manner.…”
Section: Discussionmentioning
confidence: 99%